Review the repeated bout effect in resistance - Meneghel, A. J.; Crisp, A. H.; Verlengia, R.; Lopes, C. R. (International Journal of Sports Science, 2013)
When we conducted a new series of exercises particularly eccentric, have different responses at both the performance and as well as in indirect markers of muscle damage, especially in untrained or not used to this type of exercise. But it is also evident that even when the exercise is performed for a period of time, their results are attenuated primarily with regard to the muscular damage, compared to the first session. This adaptation has been reported in the literature as Repeated Bouts Effects (RBE). The RBE has been approached in various ways is kind of contractions, actions, intensity, repetitions, speed of execution, muscle groups. The duration of the protective effect is also one of the aspects discussed which is being processed from days to months, but the rest of the effect appears to be influenced by the magnitude of muscle damage in the initial session. Theories of the mechanism of neural adaptations, cellular and mechanical, are presented and responsible for RBE, although these theories require further investigation. The purpose of doing this review is to demonstrate the importance that the magnitude of muscle damage RBE is the most efficient intervention prescient.